SIDRA: a Flexible Web Search System - Costa, Miguel (2009)
Sidra is a new indexing, searching and ranking system for Web contents. It has a flexible, parallel, distributed and scalable architecture. Sidra maintains several data structures that provide multiple access methods to different data dimensions, giving it the capability to select results reflecting search contexts. Its design addresses current challenges of Web search engines: high performance, short searching and indexing times, good quality of results, scalability and high service availability